1996
DOI: 10.1007/bf00029424
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ultraviolet irradiation on P680+ reduction in PS II core complexes measured for individual S-states and during repetitive cycling of the oxygen-evolving complex

Abstract: Flash-induced absorbance measurements at 830 nm on both nanosecond and microsecond timescales have been used to characterise the effect of ultraviolet light on Photosystem II core particles. A combination of UV-A and UV-B, closely simulating the spectrum of sunlight below 350 nm, was found to have a primary effect on the donor side of P680. Repetitive measurements indicated reductions in the nanosecond components of the absorbance decay with a concomitant appearance and increase in the amplitude of a component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Studies on a variety of plants have identified RUB-ISCO (Nogués andBaker 1995, Lesser 1996a, b) and the donor and/or acceptor side of PSII reaction centers (Post et al 1996, Vass et al 1996 as key photosynthetic targets. Especially significant for this work, Sagert et al (1997) demonstrated that the daily midday decline in efficiency of active PSII centers in upper and lower eulittoral populations of C. crispus was stimulated by the presence of natural UVR.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on a variety of plants have identified RUB-ISCO (Nogués andBaker 1995, Lesser 1996a, b) and the donor and/or acceptor side of PSII reaction centers (Post et al 1996, Vass et al 1996 as key photosynthetic targets. Especially significant for this work, Sagert et al (1997) demonstrated that the daily midday decline in efficiency of active PSII centers in upper and lower eulittoral populations of C. crispus was stimulated by the presence of natural UVR.…”
Section: Discussionmentioning
confidence: 99%
“…Redox changes in the manganese cluster of such core complexes have been studied using UV difference absorption spectroscopy and ESR (van Leeuwen et al 1992(van Leeuwen et al , 1993. This work forms part of a broader investigation of the effects on PS II of ultraviolet radiation (Post et al 1996) and solvent interactions. It is also of considerable interest to compare these kinetics with those for PS II membrane fragment preparations such as BBY preparations in order to study the effects of differing interactions of extrinsic proteins and antennae molecules with the PS II reaction center for different preparations.…”
Section: Introductionmentioning
confidence: 99%
“…The exact mechanism of UV-B radiation on PSII is still controversial. However, due to several studies with in vitro systems, there is a consensus that the donor side, most likely the Mn cluster of water oxidation, seems to be the major target site of UV-B damage (Renger et al 1989;Post et al 1996;Vass and Govindjee 1996). Beside damage to the water-oxidising complex, modification or damage at the accessory electron donor tyrosine of PSII (Y D ) and redox-active electron donor tyrosine of PSII (Y Z ) has also been observed (Yerkes et al 1990;.…”
Section: Introductionmentioning
confidence: 92%